Satu Misi dalam Dua Persimpangan: Dilema Transformasi Sosial Gereja melalui Pemberdayaan Ekonomi Jemaat - Punuh, Waraney Alfonsus Matthew (STT Transformasi Indonesia Manado, 2024)
This study provides a critical examination of the dilemmas encountered by churches in their efforts to empower the economic well-being of their congregants as part of a broader social transformation. Traditionally, churches have tended to distance themselves from business engagements, confronting substantial challenges when their members seek tangible economic support. This research employs the framework of entrepreneurial theology to explore the complexities of social transformation within the practical implementation of church missions. A qualitative approach is utilized, with a comprehensive literature review of pertinent texts to investigate this phenomenon. The findings reveal that churches can play an active role as facilitators in economic empowerment while maintaining a principled distance from business activities that might jeopardize their spiritual integrity. Through a nuanced understanding of entrepreneurial theology, churches are positioned to develop innovative programs that foster economic self-reliance among congregants, while concurrently reinforcing spiritual and social bonds within the community. These insights offer a novel perspective for churches aiming to effectively address the economic needs of their members without compromising their core mission of witness.